2005
DOI: 10.1021/ac050696k
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Proxy for Past Surface UV-B Irradiation:  A Thermally Assisted Hydrolysis and Methylation py-GC/MS Method for the Analysis of Pollen and Spores

Abstract: A method was developed for the analysis of the UV-absorbing sporopollenin monomers p-coumaric acid and ferulic acid in very low numbers of pollen. This enables the analysis of pollen or spores from cultured plants, from herbarium collections, and from sediment, soil, and peat cores. The method involves thermally assisted hydrolysis and methylation using tetramethylammonium hydroxide combined with gas chromatography and mass spectrometry. Pyrolysis, gas chromatographic, and mass spectrometric conditions were op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
72
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(76 citation statements)
references
References 13 publications
(18 reference statements)
1
72
0
Order By: Relevance
“…For reconstructing UV-B flux, oxidation removes UV-B absorbing compounds (UACs) that are present in the protoplasm and bound to the exine, reducing the concentration to those that are present in the exine itself (Rozema et al, 2001a;Blokker et al, 2005). Rozema et al (2001a) estimated that 57% of UV-B absorbance in Helleborus foetidus pollen occurs in the exine; in Betula pendula 41% occurs in the exine.…”
Section: Results Physical Changesmentioning
confidence: 99%
See 1 more Smart Citation
“…For reconstructing UV-B flux, oxidation removes UV-B absorbing compounds (UACs) that are present in the protoplasm and bound to the exine, reducing the concentration to those that are present in the exine itself (Rozema et al, 2001a;Blokker et al, 2005). Rozema et al (2001a) estimated that 57% of UV-B absorbance in Helleborus foetidus pollen occurs in the exine; in Betula pendula 41% occurs in the exine.…”
Section: Results Physical Changesmentioning
confidence: 99%
“…However, there is currently much less of an understanding of how oxidation affects sporomorph chemistry, and what this means for recovering information on UV-B flux and plant taxonomy from standard palynological preparations, and from fossil sporomorphs that have undergone natural oxidation prior to burial. Previous studies (Hemsley et al, 1996;Rozema et al, 2001a;Blokker et al, 2005) have demonstrated a decline in the concentration of aromatic compounds (including UV-B absorbing phenolic compounds) in sporomorphs following oxidation. However, it is not clear if these chemical changes represent alteration of the exine or simply loss of the protoplasm, intine and outer compounds, or whether different oxidation methods affect sporomorph and sporopollenin chemistry in similar ways, and these questions are yet to be comprehensively addressed in a rigorous experimental framework.…”
mentioning
confidence: 98%
“…Because the ms1 mutant anther formed lignin structure similar to that of wild-type anther (see Supplemental Figure 2 online), the genes affected by ms1 are likely important for the synthesis of lignin-like compounds, but not lignin. Therefore, we hypothesize that these putative phenylpropanoid synthetic gene products can catalyze novel reactions leading to sporopollenin monomers, such as p-coumaric acid and ferulic acid (Blokker et al, 2005). In addition, we have identified three groups of putative MS1 downstream genes with putative lipid biosynthetic functions (Table 1).…”
Section: Putative Sporopollenin Biosynthetic Genes Regulated By Ms1mentioning
confidence: 99%
“…While recent progress has been made in understanding the structure and biosynthesis of two other major aliphatic-based polyester extracellular matrices that share many similarities to sporopollenin (i.e., cutin and suberin) (reviewed in Franke and Schreiber, 2007;Pollard et al, 2008), the structure and monomeric composition of the exine and the sporopollenin polymer remain largely unknown due to the small amounts of material made during microspore and pollen grain development, the recalcitrance of exine to chemical degradation, and the limited number of techniques available for exine chemical analysis (Dominguez et al, 1999;Bubert et al, 2002;Ahlers et al, 2003;Blokker et al, 2005). Available data from several plants indicate that the major monomeric components of the sporopollenin polymer are polyhydroxylated, unbranched long-chain, and/or very-long-chain fatty acids, as well as oxygenated aromatic compounds, likely derived from phenylpropanoid acids, such as p-coumaric, caffeic, and/or ferulic acids (Guilford et al, 1988;Ahlers et al, 1999;Dominguez et al, 1999;Ahlers et al, 2000;Blackmore et al, 2007).…”
Section: Introductionmentioning
confidence: 99%